On recursive stopping of decimation of discrete-time bandlimited signals - Pupeikis, Rimantas (Lietuvos matematikos rinkinys, 2011)
For each non-decimated as well as decimated realization discrete-time Fourier series coefficient values, located at Nyquist frequency are calculated, using original speedy recursive expressions based on reverse order processing of the given realizations. The criterion for stopping of multifold decimation of discrete-time bandlimited signals has been developed. The simulation results for the bandlimited signal with a triangularshaped spectrum are presented.
Keywords: Digital signal processing (DSP); Fourier coefficients; Nyquist frequency; decimation; discrete-time signals; stopping